Analisis Pengaruh Platform LinkedIn Terhadap Fenomena Fear of Missing Out (FOMO) di Kalangan Mahasiswa ITS - Nadya Benanda; Nadhira Apta Maheswari; Nadhyra Haninda Putri; Safia Ailsa Egasmara; Yasmin Nurul Maulidia; Nur Aini Rakhmawati (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Fear of Missing Out (FOMO) has received a lot of attention in today's digital culture, especially among students. The purpose of this research is to investigate the impact of LinkedIn usage on the level of FOMO among students at the Sepuluh Nopember Institute of Technology (ITS). Using an integrated methodology, the data was collected through surveys by questionnaire to understand the relationship between LinkedIn usage and FOMO. The information was gathered through incidental sampling from a total of 100 respondents, ranging from 2018+ students to 2023 students.According to the results, more than half of the respondents experience FOMO when seeing other people's LinkedIn profiles. Based on the results, it shows that students feel more motivated to do something more productive because of their FOMO. These results are expected to assist practitioners, educators, and academics interested in FOMO and the use of social platforms in higher education to gain a better understanding of how the LinkedIn platform affects the amount of FOMO among ITS students.